Physics laboratory management: Implementing project-based learning to support learning at UHAMKA - Ermawati, Imas Ratna; Sugianto, Sugianto; Hartini, Tri Isti; Sitorus, Onny Fitriana; Dasmo, Dasmo; Sari, Nuraini Nanda (International Journal of Innovative Research and Scientific Studies, 2025)
This study aims to analyze the effect of the implementation of the Project-Based Learning model on improving the quality of physics laboratory management, Faculty of Teacher Training and Education UHAMKA. The study focused on five main aspects of laboratory management, namely planning practical activities, organizing tools and materials, implementing activities, evaluating practical results, and documentation and reporting. This type of research uses a quantitative approach with a pretest-posttest one group design. The methods used to collect data are observation, documentation, and questionnaires conducted on 22 students who are currently taking physics practical courses in the odd semester of 2024-2025. The research instruments are in the form of observation sheets and laboratory management assessment questionnaires that have been validated by experts. Data were analyzed using descriptive-comparative statistics by calculating the average score before and after the implementation of project based learning, as well as the percentage increase in each aspect. The results showed that all aspects of laboratory management improved after the implementation of the project based learning model. The highest increase occurred in the documentation and reporting aspect at 19%, followed by planning practical activities at 18%, evaluating practical results at 17%, implementing activities at 15%, and organizing tools and materials at 14%. The conclusion of this study is that project-based learning can improve students’ abilities to plan, implement, and evaluate laboratory activities systematically, collaboratively, and reflectively.